2020
DOI: 10.1126/scitranslmed.abb3336
|View full text |Cite
|
Sign up to set email alerts
|

Cardiosphere-derived exosomal microRNAs for myocardial repair in pediatric dilated cardiomyopathy

Abstract: Although cardiosphere-derived cells (CDCs) improve cardiac function and outcomes in patients with single ventricle physiology, little is known about their safety and therapeutic benefit in children with dilated cardiomyopathy (DCM). We aimed to determine the safety and efficacy of CDCs in a porcine model of DCM and translate the preclinical results into this patient population. A swine model of DCM using intracoronary injection of microspheres created cardiac dysfunction. Forty pigs were randomized as preclini… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
43
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 65 publications
(45 citation statements)
references
References 48 publications
1
43
0
1
Order By: Relevance
“…Moreover, these EV-primed fibroblasts, or the EVs themselves, were therapeutic in rat chronic MI, resulting in improved left ventricular ejection fraction, reduced scarring, and increased microvessel density [ 207 ]. Similar results were obtained after administration of human CDC EVs in porcine models of acute or chronic MI [ 208 ] or pediatric dilated cardiomyopathy [ 209 ]. Wnt/β-catenin signaling in the CDC was critical for the potency of CDC and proposed to enhance an antifibrotic EV miR-92- BMP pathway [ 210 ].…”
Section: Cardiac Fibrosissupporting
confidence: 78%
See 1 more Smart Citation
“…Moreover, these EV-primed fibroblasts, or the EVs themselves, were therapeutic in rat chronic MI, resulting in improved left ventricular ejection fraction, reduced scarring, and increased microvessel density [ 207 ]. Similar results were obtained after administration of human CDC EVs in porcine models of acute or chronic MI [ 208 ] or pediatric dilated cardiomyopathy [ 209 ]. Wnt/β-catenin signaling in the CDC was critical for the potency of CDC and proposed to enhance an antifibrotic EV miR-92- BMP pathway [ 210 ].…”
Section: Cardiac Fibrosissupporting
confidence: 78%
“…Overexpression of β-catenin and Gata4 in fibroblasts imparted therapeutic properties on the cells or their EVs as shown by, respectively, improved survival and heart function in mouse MI models or functional improvement and anti-fibrotic effects in the skeletal muscle of the mdx mouse model of Duchenne muscular dystrophy [ 210 ]. In the dilated cardiomyopathy model, the improvement in cardiac function and reduced fibrosis was attributed to the enrichment in CDC EVs of proangiogenic and cardioprotective miRs including miR-146a-5p which attenuated fibrosis by reducing inflammation and apoptosis through its targeting of TRAF6/Smad4/FOS [ 209 ]. CPC-derived exosomes also resulted in improvement of heart function and reduced apoptosis and fibrosis when administered to a mouse model of doxorubicin-induced dilated cardiomyopathy [ 211 ] and the therapeutic outcome was improved by conjugation of the exosomes with cardiac homing peptide which targets ischemic myocardium [ 212 ].…”
Section: Cardiac Fibrosismentioning
confidence: 99%
“…Several miRNAs such as miR-126-5p, miR-132-3p, miR-146a-5p, miR-181b, miR-210-3p, and miR-451a, known to induce antifibrotic, antiapoptotic, and proangiogenic properties, were found to be enriched in CDC exosomes from both human and swine compared to human cardiac fibroblast (HCF) exosomes. Pretreatment of CDCs with exosome inhibitor GW4869 abrogated the cardiac-protective functions of CDCs [ 35 ], confirming the role of their exosomes. The inhibition of specific pro-inflammatory and antiangiogenic miRNAs such miRNA 375 and miRNA 377 in bone marrow progenitor cells likely restricts the transfer of these miRNAs into the progenitor cell exosomes.…”
Section: Biology Of Exosomesmentioning
confidence: 84%
“…Moreover, sequencing human serum exosomes has revealed an abundance of circular RNAs within them [ 34 ]. A recent study demonstrated that swine cardiosphere-derived cells (CDCs) improved cardiac functions in a swine model of dilated cardiomyopathy (DCM), and this functional improvement was found to be associated with their miRNA composition [ 35 ]. Several miRNAs such as miR-126-5p, miR-132-3p, miR-146a-5p, miR-181b, miR-210-3p, and miR-451a, known to induce antifibrotic, antiapoptotic, and proangiogenic properties, were found to be enriched in CDC exosomes from both human and swine compared to human cardiac fibroblast (HCF) exosomes.…”
Section: Biology Of Exosomesmentioning
confidence: 99%
“…The lipid membrane structure of exosomes is similar to that of liposomes. Thus, exosome can protect nucleic acids from degradation, and facilitate transport of miRNAs, mRNAs, and proteins to receptor cells with no virulence and adverse immunogenicity [14][15][16] . Genetic engineering of miRNA in exosomes can further enhance the protective effects on different diseases 17,18 .…”
mentioning
confidence: 99%